2017
DOI: 10.18203/2320-6012.ijrms20173552
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic detection of carbapenem resistance in gram negative bacilli from various clinical specimens of a tertiary care hospital in Western Uttar Pradesh

Abstract: Background: Carbapenemase producing multidrug-resistant organisms (i.e., MDROs) is a critical medical and public health issue globally. These bacteria are often resistant to all beta-lactam agents and are also co-resistant to other multiple classes of antimicrobial agents, leaving very few antimicrobial options.Methods: This study was carried out at UP University of medical sciences Saifai, Etawah, Uttar Pradesh, India, from January 2015 to June 2016. 110 isolates were found resistant by the Kirby Bauer’s disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
2
7
1
Order By: Relevance
“…Carbapenemase-producing micro-organisms are difficult to detect and require phenotypic and genotypic analyses. Of the 220 isolates, 207 (94.0%) had phenotypic positivity, which was comparable to that reported by Diwakar et al 20 Our genotypically positive findings (87.2%) were comparable to the genotypically positive rate of 90.3% reported by Garg et al 21 The major differences were likely due to geographic region, the testing method used, and the organism. 22…”
Section: Discussionsupporting
confidence: 87%
“…Carbapenemase-producing micro-organisms are difficult to detect and require phenotypic and genotypic analyses. Of the 220 isolates, 207 (94.0%) had phenotypic positivity, which was comparable to that reported by Diwakar et al 20 Our genotypically positive findings (87.2%) were comparable to the genotypically positive rate of 90.3% reported by Garg et al 21 The major differences were likely due to geographic region, the testing method used, and the organism. 22…”
Section: Discussionsupporting
confidence: 87%
“…26 Our study is nearly similar to the study of Sharma et al in 34,9 Regarding Enterobacteriaceae, this is nearly similar to the study of Kaur et al in India and Diwakar et al in India. 28,35 But our study is nearly dissimilar to the study of Barai et al in Bangladesh and Pawar et al in India. 34,36 In this study, all the carbapenemase-producing strains of Enterobacteriaceae are 100% resistant to ceftriaxone, cefotaxime, and `ceftazidime.…”
Section: Specimencontrasting
confidence: 80%
“…The prevalence of carbapenem resistant Enterobacteriaceae, Acinetobacter baumannii and Pseudomonas aeruginosa in Bangladesh were 9.8%, 55% and 53.7% respectively, in India were 44.3%, 56% and 10% respectively and in US were 18%, 22% and 60.3% respective. 5,6,7,8,9,10 Regarding the antimicrobial resistance rates of Carbapenemase-producing Enterobacteriaceae in Bangladesh to third generation cephalosporins 80%-100%, fluoroquinolones, aminoglycosides, monobactam 60%-80% , to the carbapenem 10%-30%. 11,12 The antimicrobial resistance rates of Carbapenemase-producing Acinetobacter baumannii in Bangladesh to third-generation cephalosporins are 90%-100%, fluoroquinolones, aminoglycosides, monobactam 70%-80%, to carbapenem 25%-60%.The antimicrobial resistance rates of Carbapenemase-producing Pseudomonas aeruginosa in Bangladesh to thirdgeneration cephalosporins are 90%-100%, to fluoroquinolones, aminoglycosides, monobactam 65%-80%, to carbapenem 15%-30%.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, we found prevalence of genes encoding for carbapenemase was 47.2%. Variable rate of genotypic prevalence has been reported by various Indian studies ranging from 18% to 100% [7][8][9][10][11]23 . The difference might be due to different target genes as in some studies only single class of gene was targeted whereas in our study common genes of all classes of carbapenemase were included.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, resistance to carbapenams becomes a real threat to the survival of patients with infections caused by MDR-GNB as mortality in such infections has been reported up to 50% who acquire blood stream infections and overall mortality rates are 21% higher than those of non resistant GNB and results in longer in patient stays and higher treatment costs 1,6 . Several Indian studies have reported prevalence of carbapenemase producing Enterobacteriaceae, Pseudomonas and Acinetobacter species in a range of 11% to 81% [7][8][9][10][11] . This study set out to determine the burden of carbapenam resistance, prevalence of carbapenemase producing organism and carbapenemase encoding gene among clinical MDR-GNB isolates obtained from patients.…”
Section: Introductionmentioning
confidence: 99%